Appositive ki Clauses in Turkish - Hasan Mesut Meral (Dilbilim Araştırmaları Dergisi, 2018)
This study explores the post-nominal appositives formed with the so called complementizer ki in Turkish. It makes two sets of arguments: (i) Post-nominal appositives formed with ki do not form a constituent with their antecedents in syntax, instead they are formed as separate clauses, having their own illocutionary act and being opaque to syntactic operations of their host clauses, hence non-integrated in the sense of Cinque (2008), (ii) Appositive ki clauses involve neither subordination, nor coordination, rather they are ForcePs adjoining to the root clause, and this root level adjunction is characterized as concatenation without labels in the sense of Horstein (2009) and Citko (2016).